Microstructure and phase evolution of the metastable β-type 51Zr-40Ti-4.5Al-4.5V alloy. (March 2017) - Ran, Jing
Abstract: The effect of heat treatment on the microstructural evolution and mechanical properties of the 51Zr-40Ti-4.5Al-4.5V (wt.%) was evaluated in the present work. The alloy was re-melted thrice by electromagnetic induction, homogenized, beta-processed, and then solubilized at different temperatures for 60 min. X-ray diffraction, optical microscopic, SEM, TEM and mechanical testing are performed to evaluated the phase compositions, microstructure and mechanical properties of the specimens under different solubilized regions. The calculated Ms of the 51Zr-40Ti-4.5Al-4.5V alloy is 700 K. The phases of as-received specimen mainly consist of α/α′, α″ martensite and β phase. After solubilization and quenching processing, the phase content of specimens changed. The α/α′ and α″ phase decomposed and transformed into β phase. At 973 and 1023 K, recrystallization occurred and the "double-yielding" was present at this case. The optimal mechanical properties was obtained at 1023 K, with approximately σb  = 1127 MPa and ε = 14.26%. Highlights: With solubilized temperatures increasing, martensite was completely transformed into β phase. Solubilizing at 700 and 750 °C, recrystallization was appearing. The optimum mechanical properties ( σ b  = 1127 MPa, ε  = 14.26%) were obtained at 750 °C.